BAGAIMANA EKONOMI ISLAM MEMANDANG HUBUNGAN ANTARA PERTUMBUHAN EKONOMI DAN PERUBAHAN IKLIM ? (STUDI KASUS: INDONESIA) - Faishol Luthfi (FAKULTAS EKONOMI DAN BISNIS UNTAN, 2023)
This study aims to examine the relationship between economic growth and climate change and how Islamic economics views this relationship. This study uses a quantitative approach with the analytical method used is Vector Autoregression (VAR). The data used in this study is Indonesia's country data for the period 1990 to 2018. The results of the study show that there is a unidirectional relationship between economic growth and climate change. This indicates that climate change, which is proxied through the amount of GHG, has affected economic growth. Climate change that has been happening for a long time due to human activities is starting to have an impact on the economic sector. Therefore, it is time for humans to be aware and think forward or visionary. Islam, through its various arguments, has explained the importance of environmental sustainability. Even more specifically, Islamic economics through the concept of hifdz al-'alam from Yusuf Qardhawi has explained the importance of preserving nature.